2014
DOI: 10.1002/hyp.10123
|View full text |Cite
|
Sign up to set email alerts
|

Snow cover estimation using blended MODIS and AMSR‐E data for improved watershed‐scale spring streamflow simulation in Quebec, Canada

Abstract: Abstract:Estimation of the amount of water stored in snow is a principal source of error for spring streamflow simulations in snow-dominant regions. Measuring this variable throughout large and often remote areas using snow surveys is an expensive task since they are practically point measurements. Remote sensing is an alternative method, which can cover much larger areas in little time, but further research is required to reduce uncertainties on snow water equivalent (SWE) estimations, especially during the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…MODIS and C-Band SAR have sometimes been used to monitor the snow cover extent of river basins, but both methods were used independently of the other and used only to map the SCA (Nagler et al, 2008;Pettinato et al, 2009). As SAR data is becoming increasingly accessible, with the free access to SENTINEL data and the future launch of the RADARSAT-Constellation, this study aims to provide a first step in developing a new tool for watershed managers, which combines the SCA, a product which demonstrated its usefulness and limitations for reservoir management (Bergeron, Royer, Turcotte, & Roy, 2014), to a second layer of information. We demonstrated that the combination of MODIS and C-Band SAR results in a snow wetness map that is more complete and useful than either method used on their own, while retaining a similar accuracy to MODIS for snow/snow-free pixels.…”
Section: Resultsmentioning
confidence: 98%
“…MODIS and C-Band SAR have sometimes been used to monitor the snow cover extent of river basins, but both methods were used independently of the other and used only to map the SCA (Nagler et al, 2008;Pettinato et al, 2009). As SAR data is becoming increasingly accessible, with the free access to SENTINEL data and the future launch of the RADARSAT-Constellation, this study aims to provide a first step in developing a new tool for watershed managers, which combines the SCA, a product which demonstrated its usefulness and limitations for reservoir management (Bergeron, Royer, Turcotte, & Roy, 2014), to a second layer of information. We demonstrated that the combination of MODIS and C-Band SAR results in a snow wetness map that is more complete and useful than either method used on their own, while retaining a similar accuracy to MODIS for snow/snow-free pixels.…”
Section: Resultsmentioning
confidence: 98%
“…Both products were obtained through the Earth Observing System Data and Information System (EOSDIS; http: //reverb.echo.nasa.Gov/). By combining them to get one product through Cara algorithm (Cara et al, 2016), and using a threshold of 30% of cloud coverage, which is the commonly used and agreement threshold for accepting or discarding information (Roy et al, 2010;Bergeron et al, 2014). 25…”
Section: Snow Covered Area Analysismentioning
confidence: 99%
“…Finally, daily SCA data derived from the spaceborne sensor MODIS/Terra are also considered (Hall et al, 2002). Because of its spatial coverage and relatively high temporal resolution, remotely sensed snow data from MODIS have proven to be valuable in a number of hydrologic studies (Bergeron et al, 2014;Roy et al, 2010;Tang and Lettenmaier, 2010;Andreadis and Lettenmaier, 2006;Clark et al, 2006), including one applied to the Nechako watershed (Marcil et al, 2016). The meteorological observations gathered over a period of 10 years (from 15 August 1990 to 14 August 2000) were used as a basis upon which a synthetic experiment (see below) tested the added value of three types of synthetic observations (streamflow, SWE and SCA) for data assimilation purposes.…”
Section: Study Area Description and Datamentioning
confidence: 99%